Studying Style in Simultaneous Interpretation - Yagi, Sane (Meta, 2000)
AbstractSeveral tools are developed to facilitate the quantitative analysis of interpretation style, a matter that has hitherto been discussed only in vague terms. These tools can allow the investigation of questions such as: How does an interpreter divide up a source language input, to what extent does he mirror a source language speaker, and to what degree does he practise reformulation? Furthermore, an adaptive monitoring instrument is devised to facilitate the graphic representation of the linear developments of a source language discourse and its simultaneous interpretation equivalent. Not only does it allow the assessment of convergence and divergence between the two discourses, but this also permits commenting on an interpreter's tempo by characterising the narrow and broad periodicity within his discourse, and on his composure and tribulation by describing his consistency and fluency in the discourse.